2018
DOI: 10.3928/01477447-20171106-03
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Internal Tibial Rotation After Anterior Cruciate Ligament Reconstruction

Abstract: The flexion angle of the knee and the position of the tibia need to be considered during tensioning of the anterior cruciate ligament (ACL) graft to avoid overconstraining the knee. The purpose of this report was to describe 2 cases of loss of tibial internal rotation after single-bundle anatomic ACL reconstruction with graft tensioning in flexion. Retrospective review of each patient's operative chart revealed that the graft was tensioned in flexion and placed in an anatomic position in the femoral tunnel at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Other authors have shown there to be a fewer degree of tibial internal rotation anatomically present in the human body compared external rotation, therefore coupling knee flexion with incremental degrees of internal tibial rotation may not produce a significant effect on medial hamstring activation. 32,33 Conversely, with lateral hamstring activation (as well as overall force output), the overall magnitude of peak muscle activation continued to decrease as the knee angle became more flexed throughout the testing range, with the greatest activation and force being generated at the most extended knee angle tested (30°). This held true for all three orientations of the tibia, and to the author's knowledge is the first time this has been shown in a controlled experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown there to be a fewer degree of tibial internal rotation anatomically present in the human body compared external rotation, therefore coupling knee flexion with incremental degrees of internal tibial rotation may not produce a significant effect on medial hamstring activation. 32,33 Conversely, with lateral hamstring activation (as well as overall force output), the overall magnitude of peak muscle activation continued to decrease as the knee angle became more flexed throughout the testing range, with the greatest activation and force being generated at the most extended knee angle tested (30°). This held true for all three orientations of the tibia, and to the author's knowledge is the first time this has been shown in a controlled experimental setting.…”
Section: Discussionmentioning
confidence: 99%